Optical band gap controlling of nanostructure Mn doped CdO thin films prepared by sol-gel spin coating method - Alahmed, Zayed A.; Albrithen, H. A.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2015)
We have grown the nanostructure Mn-doped CdO films by sol gel spin coating method. The structural and morphology properties of the Mn doped CdO films were characterized by atomic force microscopy and X-ray diffraction method. The Mn doped CdO films are formed from the nanoparticles and the particle size is controlled with manganese content. The crystal structure of undoped and Mn-doped CdO films is a cubic sodium chloride structure, showing two main characteristic peaks assigned to the (1 1 1) and (2 0 0) planes. X-ray diffraction results indicate that the Mn doped CdO films are nanomaterials with an average crystallite size of 22-25 nm. The optical band gap (E-g) values of undoped and Mn-doped CdO films were found to be in the range of 2.23-2.58 eV and E-g values of the CdO films are increased with Mn dopant up to 6% Mn. The obtained results indicate that the structural and optical properties of the CdO film can be controlled by Mn doping. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Semiconductors; Sol-gel growth; Optical properties